A fully integrated differential impulse radio transmitter - He, Jin (2013)
This paper presents a fully integrated differential impulse radio transmitter for ultra-wideband (UWB) applications. The design features low power dissipation, simple hardware, and a precise differential pulse shape. The transmitter employing the time hopping pulse position modulation (TH-PPM) scheme supports eight simultaneous users’ access with 2.5-ns hopping time allocated in a frame time of 20 ns. A differential 5th-derivative Gaussian pulse generator (PG) is designed for the first time to regulate the pulse shape so as to automatically satisfy the Federal Communications Commission (FCC) spectrum mask. The transmitter in a 1.8-V 0.18-μm CMOS process is realized in an IC area of 629 μm × 797 μm for its all digital circuit design. The measured digital pulse width of the TH-PPM pulse train is 2.5 ns and the measured 5th-derivative Gaussian pulse has a peak-to-peak amplitude of 154 mV and a pulse width of 820 ps. The power dissipation of the transmitter is 23 mW.